INTRODUCTION OF NET TUNNEL IN THE PRODUCTION OF ORANGE FLESHED SWEET POTATO SEED (VINES) IN OYUN LOCAL GOVERNMENT OF KWARA STATE. - SALAWU, I.A.; BELEWU , Y.K.; ABIMBOLA, O.O.; ALFONSO, O.C. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2023)
This study investigated the potential use of net tunnels for an adequate supply of sweet potato vines, increasing farmer access to quality vines and lowering the cost of maintaining virus-free planting material on the farm. A structured questionnaire was used in collecting information from respondents. Data were analyzed using linear regression and descriptive statistics. Primary data collected from 80 randomly selected farmers from the study area revealed that 72.5% of the respondents were males and most of the farmers attained higher educational levels with 42.50% and 28.75% for secondary and tertiary school levels respectively. The results also show that a larger percentage 23.75% of the respondents obtained their planting materials from informal sources. The farmers’ willingness to use net tunnels in terms of their maintenance and simplicity in their construction revealed the mean value of 4.49 and 4.39 respectively. The study also revealed that easiness in maintaining net tunnel, low cost of the technology and market availability for the planting materials all determined the willingness of adoption of net-tunnel technology. The socio-economic factors; membership in agricultural association, farm size of the respondents, and source of capital significantly influenced the farmers’ willingness in the adoption of net the technology for OFSP planting material production. However, membership in agricultural association consistently contributed significantly to the factors determining willingness of adoption of net-tunnel technology of the farmers in Oyun Local Area of Kwara State.